Case study: Possible differences in phthalates exposure among the Czech, Hungarian, and Slovak populations identified based on the DEMOCOPHES pilot study results - Černá, Milena; Malý, Marek; Rudnai, Peter; Középesy, Szilvia; Náray, Miklós; Halzlová, Katarina; Jajcaj, Michal; Grafnetterová, Anna; Krsková, Andrea; Antošová, Danuše; Forysová, Kateřina; Den Hond, Elly; et al. (Environmental research, 2015)
OBJECTIVE: Phthalates and their metabolites are classified as endocrine modulators. They affect the hormonal balance in both children and adults. The aim of this publication was to compare the urinary levels of phthalate metabolites in selected populations of the Czech Republic (CZ), Slovakia (SK), and Hungary (HU) in relation to the sources of phthalate exposure identified by means of questionnaire (personal care products, floor and wall coverings, plastic toys, and some kinds of foods). METHODS: Data were obtained through the twin projects COPHES (COnsortium to Perform Human biomonitoring on a European Scale) and DEMOCOPHES (DEMOnstration of a study to COordinate and Perform Human biomonitoring on a European Scale) from 2009 to 2012. The target groups were children aged 6-11 years old and their mothers up to 45 years of age. The metabolites of phthalates (monomethyl phthalate (MMP), monoethyl phthalate (MEP), monobenzyl phthalate (MBzP), mono-cyclohexyl phthalate (MCHP), mono-(2-ethylhexyl) phthalate (MEHP), mono-(2-ethyl-5-hydroxyhexyl) phthalate (5OH-MEHP), and mono-(2-ethyl-5-oxohexyl) phthalate (5OXO-MEHP)) were analysed in first morning urine samples. After enzymatic glucuronide cleavage, the urine sample analyses were performed using ultra-high-performance liquid chromatography-electrospray ionization tandem mass spectrometry (UHPLC-ESI-MS/MS) in one laboratory that qualified in the External Quality Assessment exercises organised by COPHES. RESULTS: Significant differences in phthalate exposure between countries were revealed for children only but not for mothers. The concentrations of 5-OH-MEHP (P<0.001), 5OXO-MEHP (P<0.001), and their sum (P<0.001) were the highest in SK compared to CZ and HU. The health based guidance values for the sum of DEHP metabolites 5-OH MEHP and 5OXO-MEHP established by the German Commission for biomonitoring of 300 µg/L and 500 µg/L for women adults and children, respectively, were only exceeded in one mother and three boys. A significant difference was also found for MEP (P=0.0149), with the highest concentrations detected in HU. In all countries, the increasing frequency of using personal care products significantly elevated the concentrations of MEP. CONCLUSION: Some differences were observed between countries in the concentrations of individual urinary phthalate metabolites in children. However, the questionnaire results give no direct explanation for the differences between the countries except the variation in using personal care products.
Keywords: kyseliny ftalové; Environmental Monitoring; Male; Slovakia; Phthalic Acids; Slovenská republika; monitorování životního prostředí; vysokoúčinná kapalinová chromatografie; Česká republika; Child; látky znečišťující životní prostředí; pilotní projekty; tandemová hmotnostní spektrometrie; dítě; Adult; dospělí; mužské pohlaví; Data Interpretation, Statistical; průzkumy a dotazníky; Smoking; Chromatography, High Pressure Liquid; Czech Republic; DEMOCOPHES; Maďarsko; lidé; ženské pohlaví; Humans; Spectrometry, Mass, Electrospray Ionization; Environmental Exposure; interpretace statistických dat; Hungary; Urinary phthalate metabolites; Environmental Pollutants; hmotnostní spektrometrie s elektrosprejovou ionizací; Pilot Projects; Tandem Mass Spectrometry; Female; Surveys and Questionnaires; lidé středního věku; kouření; vystavení vlivu životního prostředí; Middle Aged